The relationship between low blood thiamin levels in diabetes to thiamin intake and diabetic control - Vindedzis, Sally Ann (Curtin University, 2008)
Mild thiamin deficiency is prevalent in diabetes, and high dose thiamin ameliorates some diabetic complications, but there are no definitive studies addressing thiamin intake, diabetes control and thiamin status in diabetes. Subjects were 113 people with diabetes (58 type 1, 55 type 2), 43 with and 70 without thiamin supplementation. Dietary thiamin was estimated by 24-hour recall, diabetes control by HbA1c. Age, BMI, albumin excretion, activity level and smoking status did not correlate with red cell thiamin (RCT) in either group. RCT correlated with serum thiamin (ST) (p < 0.01). In those unsupplemented, adequate dietary thiamin did not ensure normal RCT, with 15.7 % of subjects below the reference range. Supplementation to intake > 4 mg/d, was significantly associated with normal RCT (p = 0.028), with 97.7% of supplemented subjects having normal RCT. Supplementation was also significantly associated with elevated serum thiamin 24 hours post supplementation, contrary to other reports. HbA1c was not significantly associated with RCT. Conclusions: In diabetes, adequate dietary thiamin does not ensure normal red cell thiamin, but supplementation to > 4 mg/day does, raising questions about actual thiamin requirements in diabetes and supporting evidence that thiamin deficiency in diabetes is not primarily due to dietary deficiency. Diabetes control was not significantly related to thiamin status.